2017
DOI: 10.1016/j.precisioneng.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A review of tangential composite and radial composite gear inspection

Abstract: This paper presents an overview of the literature on tangential composite and radial composite gear inspection. It demonstrates -by dealing with their origins and key milestones in their history and development -the important role that inspections play in terms of the functional nature of the gears concerned. This comprehensive consideration of the subject also attempts to demonstrate how the lack of clear guidelines and standards designed to unify the criteria applied to testing, the interpretation of results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The piece of equipment was completely assembled, including drives, encoders and PC connections. The validation of measuring of this machine tool was develop using the standard of calibration procedures of Gear Measuring Instruments (GMI) and Coordinate Measuring Machines (CMM), as there are no specific regulations to cover this type of testing (Pueo et al 2017). First, the eccentricity of the axes, the squareness between them and the displacement guides were verified and adjusted (Figure 14a).…”
Section: Assembly and Validation Testingmentioning
confidence: 99%
“…The piece of equipment was completely assembled, including drives, encoders and PC connections. The validation of measuring of this machine tool was develop using the standard of calibration procedures of Gear Measuring Instruments (GMI) and Coordinate Measuring Machines (CMM), as there are no specific regulations to cover this type of testing (Pueo et al 2017). First, the eccentricity of the axes, the squareness between them and the displacement guides were verified and adjusted (Figure 14a).…”
Section: Assembly and Validation Testingmentioning
confidence: 99%
“…The results of these tests include the sum of various simultaneous influences [8][9][10] and allow establishing the accuracy grade of the gear and obtaining geometric information. Recent studies have been identified related to gear rolling tests, both radial and tangential composite [11][12][13][14]. This is why the estimation of rolling tests uncertainty is of paramount importance for understanding and optimizing the measurement process with this type of machines.…”
Section: Introductionmentioning
confidence: 99%
“…This fact also hinders its application to other types of gears' transmission. All of it allows considering the rolling testers as repeatable but not comparable because of the lack of traceability in the test results [14].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, they have been widely used in industry for decades, mainly as controls during the production process [6]. Nowadays, there is a growing interest in studies and developments of new gear measurement techniques and instruments, based on rolling principles, due to its potential in industry [7][8][9].…”
Section: Introductionmentioning
confidence: 99%